How Oil Price Changes Affect Foreign Direct Investment Inflows in South Africa? An ARDL Approach - Tala, Lavisa; Hlongwane, Tshembhani M. (International Journal of Economics and Financial Issues, 2023)
The study examined how oil price changes affect Foreign Direct Investment (FDI) inflow in South Africa. The study used annual quantitative data, obtained from the South African Reserve Bank (SARB) and World Bank development indicators. With the exception of real exchange rate, Augmented Dicky Fuller (ADF) and Phillips-Peron (PP) tests for stationarity indicated variables become stationary after first differencing. Stationarity test results suggested application of ARDL bounds test for cointegration. ARDL bounds test for co-integration confirms that variables of the study have long-run relationship with F-statistic of 6.59, which is higher than the lower (2.98) and upper (3.78) boundaries at least 5% level of significance. In the long - run oil prices coefficient found to have negative and significant influence in foreign direct investment inflows during 1980-2020 period. Empirical results provide practical implications for South Africa, as oil importing country can hedge crude oil price changes to maintain future quantity of crude oil to be imported. The study recommends expansion of renewable energy sources to reduce South Africa’s vulnerability to oil price fluctuations. Moreover, since oil prices are exogenously determined, setting up forward looking institutions such as sovereign wealth funds and short- term stabilization funds will be better.